Control Agents Of Environmentally Friendly Plant Disordering Organisms (Opt) Used Vegetable Farmers In Tomohon City - Enderika Enus; Elisabeth R. M. Meray; Jimmy Rimbing; Sofia Wantasen; Defly A. S. Turang (Jurnal Agroekoteknologi Terapan, 2022)
This research on Environmentally Friendly Control Agents for Plant-Disturbing Organisms (PDOs) Used by Vegetable Farmers aims to identify the kind eco-friendly control agents used by vegetable farmers in the city of Tomohon to cope with Plant-Disturbing Organisms. This study uses survey as its method which was conducted via questionnaire. Forty farmers were surveyed and directly interviewed. The data collected from these questionnaires were then calculated in order to gain the percentage value and displayed in the form of a diagram.The result of this research indicates that only a small number of vegetable farmers in the city of Tomohon use environmentally friendly control agents for plant-disturbing organisms (PDOs). This is made possible due to the fact that both the scarcity of information regarding environmentally friendly control agents (PDOs) and its availability are limited. Keywords: Controlling agents, environmentally friendly AbstrakPenelitian mengenai Agen-agen Pengendali Organisme Penggangu Tanaman (OPT) Ramah Lingkungan Yang Digunakan Petani Sayuran Penelitian ini bertujuan untuk mengetahui agen-agen pengendali Organisme Penggangu Tanaman (OPT) ramah lingkungan yang digunakan petani sayuran di Kota Tomohon. Penelitian ini menggunakan metode survei. Survei dilakukan dengan menggunakan kuesioner. Petani yang disurvei sebanyak empat puluh orang, wawancara langsung kepada petani melalui kuesioner. Pengumpulan data kuesioner kemudian dihitung nilai presentase dan ditampilkan dalam bentuk diagram.Hasil penelitian ini menunjukkan bahwa petani sayuran di Kota Tomohon dari ke-4 jenis tanaman yang disurvei baru sebagian kecil yang menggunakan agen pengendali organisme pengganggu tanaman (OPT) ramah lingkungan. Hal ini dimungkinkan karena baik informasi maupun ketersediaan agen-agen pengendali (OPT) ramah lingkungan yang masih sangat terbatas.Kata kunci : Agen-agen pengendali, ramah lingkungan